Smart or selfish: when smart guys finish nice - Lohse, Johannes (Journal of behavioral and experimental economics, 2016)
This paper examines the relationship between public good game (PGG) contributions and cognitive abilities assessed by the Cognitive Reflection Test (CRT). Employing two additional treatment conditions, the paper explores (i) whether CRT-scores are linked to preferences for cooperation or to a better understanding of the incentive structure; and (ii) the association between CRT-scores and contributions, if choices are elicited under time pressure. A time limit should make it harder for participants to base their choices on cognitive reflection. I find a strong and positive relationship between CRT-scores and contributions in a standard one-shot PGG. This relationship is fully moderated by the presence of time pressure. Thus, features of the decision environment can affect the link between cognitive abilities and PGG contributions. Finally, there is only a weak relationship between CRT-scores and the ability to understand the incentive structure. (PsycINFO Database Record (c) 2019 APA, all rights reserved)